Pengaruh Literasi Digital, Pengetahuan Kewirausahaan Dan Dukungan Sosial, Terhadap Kesiapan Berwirausaha Santri PP. Anwarul Huda Malang - Fiqrianto, Mohamad Iqbal; Wahono, Budi; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to test and explain the influence of digital literacy, entrepreneurial knowledge and social support on the entrepreneurial readiness of students at the Anwarul Huda Islamic boarding school. The sample used in this research was 134 respondents using a purposive sampling method with the Slovin formula technique. The data analysis method is quantitative using multiple linear regression analysis. The data used is a partial hypothesis test (t test). The research results show that partially (t test) the variables digital literacy, entrepreneurial knowledge and social support influence the entrepreneurial readiness of students at the Anwarul Huda Islamic boarding school. Keywords: Digital Literacy, Entrepreneurial Knowledge And Entrepreneurial Readiness